Acute myeloid leukaemia presenting as cholestatic hepatitis. Issue 5 (27th April 2004) - Wandroo, F A; Murray, J; Mutimer, D; Hubscher, S
Abstract : A 40 year old man presented with abdominal pain, jaundice, weight loss, and hepatosplenomegaly. Liver function tests revealed cholestatic jaundice and a computed tomography scan showed an enlarged liver, with a normal biliary tree. Liver biopsy showed diffuse infiltration by neutrophils, monocytoid cells, and blasts. Peripheral blood film and bone marrow were consistent with acute myeloid leukaemia. After treatment with chemotherapy using an acute myeloid leukaemia protocol (UK Medical Research Council AML-12), there was complete resolution of jaundice and the patient went into complete molecular remission.